Antidepressant and anxiolytic potential of Citrus reticulata Blanco essential oil: a network pharmacology and animal model study - Khanh Nguyen, Nhi Phuc; Kwon, Ji-Hye; Kim, Min-Kyung; Tran, Khoa Nguyen; Huong Nguyen, Ly Thi; Yang, In-Jun (Frontiers in Pharmacology, 2024)
Citrus reticulata Blanco essential oil (CBEO) has attracted attention as a potential treatment for depression and anxiety.There is limited evidence regarding the active compounds responsible for its therapeutic effects. Additionally,substantial amounts of CBEO and prolonged therapy are often required.This study aims to investigate rapid-acting antidepressant and anxiolytic effects of CBEO, identify the underlying composition, optimize its dosage and duration.Methods: CBEO composition was determined using GC-MS, and targets were obtained from SwissTargetPrediction.Depression-related targets were collected from DisGeNET, GeneCards, TTD, and OMIM.Overlap between CBEO and depression targets was utilized to build a network diagram.STRING database facilitated the construction of a proteinprotein interaction network,Topological analysis predicted main antidepressant active ingredients in CBEO.A mixture of these compounds was prepared based on GC-MS ratios.TST, EPM, corticosterone-induced PC12, lipopolysaccharide (LPS)-induced BV2 cells were used to validate antidepressant, anxiolytic potential of CBEO and CBEO's bioactive constituents.Results: CBEO contains 18 components that target 121 proteins.We identified 595 targets associated with depression; among them, 29 targets were located between essential oils and depression.Topological results revealed linalool,p‐cymene,α‐terpinene,terpinen‐4‐ol,α‐terpineol were the major active compounds of CBEO in the management of depression.GO analysis identified G protein-coupled opioid receptor activity, phospholipase C-activating G protein-coupled receptor, neuron projections that were mostly related to molecular functions, cellular components, and biological processes.Neuroactive ligand-receptor interactions,chemical carcinogenesis,calcium signaling pathways were the major pathways identified in KEGG analysis.Molecular docking showed that the main bioactive ingredients of CBEO had favorable binding affinities for Protein-Protein Interaction's hub proteins, including OPRM1,PTGS2,ESR1,SLC6A4, DRD2,NR3C1.These five compounds were then mixed at 0.8:5:0.6:2:1 (w/w) ratio to form a CBEO antidepressant active compound mixture.An acute intranasal treatment of CBEO (25 mg/kg) only demonstrated an antidepressant effect, whereas the main bioactive compounds combination (12.5 mg/kg) illustrated both antidepressant and anxiolytic effects in mice.Linalool,p-cymene,terpinene-4-ol exhibited neuroprotective and antineuroinflammation in the in vitro study,while these effects were not observed for α‐terpinene and α‐terpineol.Linalool,p‐ cymene,α‐terpinene,terpinen‐4‐ol,α‐terpineol might be contributing to CBEO's antidepressant effect by regulating neuroactive ligand-receptor interaction,neuron projection,and receptor signaling pathway.A mixture of these compounds showed rapid antidepressant potential via intranasal administration, which was comparable to that of CBEO.The mixture also exhibited an In review anxiolytic effect while not seen in CBEO.